Suppression of seed production as a long-term strategy in weed biological control: The combined impact of two biocontrol agents on Acacia mearnsii in South Africa - Impson, F.A.C.; Kleinjan, C.A.; Hoffmann, J.H. (Biological control, 2021)
•Two biocontrol agents reduce seeding of Acacia mearnsii to extremely low levels.•The reduction is primarily due to a flower-galling midge, Dasineura rubiformis.•A seed-feeding weevil, Melanterius maculatus, plays a supplementary role.•No immediate change in the extent of existing infestation is expected.•Rates of spread of the weed should be curtailed. The effectiveness of seed-reducing biocontrol agents, particularly for perennial trees with long-lived seed banks, remains a subject of debate. General consensus is that exceptionally high and consistent levels of damage are required to have any meaningful impact. In South Africa two seed-reducing agents are deployed against Acacia mearnsii, a woody mimosoid whose invasive success is attributed to high fecundity and the accumulation of persistent soil-stored seed banks. This study demonstrates that seed production has declined to extremely low levels, primarily due to a flower-galling midge, Dasineura rubiformis (Cecidomyiidae), with a seed-feeding weevil, Melanterius maculatus (Curculionidae), playing a supplementary role. No short to medium term impacts on the current density, extent or abundance of the weed are anticipated because there are sizeable seed banks in the soil which will continue to replenish any aboveground losses for many years to come. However, the dramatic reductions in annual levels of seed-fall that have been realised are anticipated to curb rates of accumulation of seed banks and curtail spread of the weed.